2011
DOI: 10.1039/c1md00206f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and activity of a novel diether phosphonoglycerol in phospholipase-resistant synthetic lipid:peptide lung surfactants

Abstract: This paper reports the chemical synthesis and purification of a novel phospholipase-resistant C16:0, C16:1 diether phosphonoglycerol with structural analogy to ester-linked anionic phosphatidylglycerol (PG) in endogenous pulmonary surfactant. This diether phosphonoglycerol (PG 1) is studied for phospholipase A2 (PLA2) resistance and for surface activity in synthetic exogenous surfactants combined with Super Mini-B (S-MB) peptide and DEPN-8, a previously-reported diether phosphonolipid analog of dipalmitoyl pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…MD runs using GROMACS () should provide valuable information on the detailed 3D-structures of SP-C mimics in the bilayer (Walther et al, 2010; Schwan et al, 2011). For simulations of SP-Css ion-lock 1 in a lipid bilayer-water box, the “0 ns” model was obtained by first templating its primary sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MD runs using GROMACS () should provide valuable information on the detailed 3D-structures of SP-C mimics in the bilayer (Walther et al, 2010; Schwan et al, 2011). For simulations of SP-Css ion-lock 1 in a lipid bilayer-water box, the “0 ns” model was obtained by first templating its primary sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the phospholipid composition in endogenous surfactant has been studied in detail, this knowledge has not been used for the development of synthetic surfactants. Phospholipase-resistant diether phosphono analogs of phosphatidylglycerol and dipalmitoylphosphatidylcholine have been used together with the SP-B analog, Super Mini-B [34] . These surfactant preparations had similar surface activity to the calf lung surfactant extract (CLSE) in vitro and are more resistant to degradation than the animal-derived surfactant preparation.…”
Section: Further Development Of Synthetic Surfactantsmentioning
confidence: 99%
“…Phospholipase degradation of exogenous surfactant phospholipids has the potential not only to reduce active drug concentration, but also to generate byproducts such as free fatty acids and lysophosphatidylcholine that are themselves severe biophysical inhibitors of surfactant activity (Wang & Notter, 1998; Holm, Wang & Notter, 1999; Hite et al, 2012; De Luca et al, 2013). We have previously reported the synthesis of active analogs of lung surfactant glycerophospholipids that have specific molecular substitutions to confer chemical resistance to phospholipase degradation (Turcotte et al, 1991; Wang et al, 2003; Notter et al, 2007; Schwan et al, 2011). The current study uses two of these phospholipase-resistant lipids, DEPN-8 and PG-1, as components in new synthetic lipid/peptide surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…DEPN-8 is a C16:0 diether phosphonolipid analog of dipalmitoyl phosphatidylcholine (DPPC) (Turcotte et al, 1991; Wang et al, 2003), and PG-1 is a C16:0:C16:1 ether-linked phosphonolipid analog of palmitoyl-oleoyl phosphatidylglycerol (POPG) (Schwan et al, 2011), the major class of anionic phospholipids in native surfactant. Prior work by our group has shown that synthetic surfactants containing DEPN-8 or 9:1 DEPN-8:PG-1 plus an active surfactant protein (SP)-B peptide (Mini-B or Super Mini-B) have significant surface activity (Walther et al, 2007; Schwan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation